(untitled) (Journal of Economic Additions, 2019)
The Algerian banking system has undergone many reforms. Nevertheless, the banking sector is still suffering from a number of shortcomings and negatives which limit the effectiveness of these reforms and turn them into achieving the desired objectives. This requires the need to adopt and work towards governance in order to improve the banking system And to qualify them for integration into the global economy. The most important resultsthat the need to apply the principles of governance in Algerian banks did not arise from nothing, but the growing interest in this concept is due to what he knew Algerian banking system of gaps, led him to exposure to tremors that destabilized the stability and credibility of the banking system. Key words: Governance, Algerian banking system, gaps, stability. JEL Classification:G38,G24,G39,C62